Employment and Labor Supply Responses to the Child Tax Credit Expansion: Theory and Evidence - Diane Whitmore Schanzenbach; Michael R. Strain (Institute of Labor Economics (IZA), 2024)
The 2021 Child Tax Credit (CTC) expansion increased government benefits to families, and especially to families with the lowest incomes. Economic theory predicts that this policy intervention would have led to a reduction in labor supply among adults in those families. Our review of available research suggests that employment within broadly defined demographic groups was not reduced by the 2021 CTC changes. However, we present evidence that employment was reduced among mothers with relatively low levels of education - the demographic group that was most affected by the CTC expansion. For the 2021 CTC expansion, theory and evidence were in the strongest alignment when the research design that produced the evidence was most focused on the demographic groups most likely to be affected by the expansion.
Keywords: H31; J08; 330; employment; labor supply; cash transfers; maternal employment; child tax credit